PAJANAN PESTISIDA SEBAGAI FAKTOR RISIKO KEJADIAN DIABETES MELLITUS PADA PETANI: SEBUAH KAJIAN SISTEMATIK - Sari, Intan Permata; Suhartono, Suhartono; Darundiati, Yusniar Hanani (Jurnal Kesehatan Masyarakat (Undip), 2021)
Diabetes mellitus is a pancreatic disorder that occurs in the long term due to the failure of the pancreatic fungtion to produce the insulin hormone. Diabetes mellitus can be stimulated by pesticide exposure due to contact between the body and pesticides that affect the hormonal system. However, there is no certainty regarding the risk factors for pesticide exposure that most influence the incidence of diabetes mellitus.  This study aimed to identify risk factors of pesticide exposure on the incidence of diabetes mellitus in farmers and used  systematic review method by searching for relevant articles on the Science Direct, Scopus, PubMed, Researchgate and Google Scholar sites. Article searches were conducted based on search keywords including diabetes mellitus, pesticide exposure, diabetes mellitus in farmers, etc. Of the 449 articles found, 8 were examined further. Each article showed p value <0.05 on the variable work period, frequency of spraying, use of PPE and type of pesticide. One of two articles using the work period and used of PPE variable showed OR>1; CI>1 in work period ≥ 20 years and bad use of PPE. Two articles that used variable frequency of spraying showed OR>1; CI>1 at spraying frequency > 1 time/week. From the four articles using variable types of pesticides, it is known that the pesticides are dieldrin, endosulfan, oxychlordane, chlordane, toxaphene, fonofos, phorate, parathion dan mevinphos, carbaryl atau sevin, aldicarb, 2,4,5-T/2,4,5-TP dan benlate showed OR>1; CI>1. Work period, frequency of pesticide spraying, use of PPE and use of certain types of pesticides are proven as risk factors for pesticide exposure that affect the incidence of diabetes mellitus in farmers.